Experimental analysis of hybrid and conventional air conditioning systems working in hot-humid climate. (25th May 2017) - Fatouh, M.; Abou-Ziyan, H.; Mahmoud, O.; Abd El-Raheim, D.
Highlights: Alumina-based hybrid system affords superior performance characteristics. Hybrid system offers excellent performance under hot very humid conditions. Hybrid system of single -layers alumina bed has better COP than triple-layer bed. Short cycle durations require lower size of cooling system but at lower system COP. Long cycle durations achieve large COP and require lower compressor power. Abstract: This paper reports the experimental performance characteristics of a hybrid air conditioning system consists of a conventional (vapor compression) system integrated with thin-multilayer activated alumina bed with single, double and triple-layers. The performance characteristics of both systems are investigated under hot very humid climate with fresh air mixing ratio from 40 to 100% that is replicated at various process air temperature (28–36 °C) and relative humidity (50–80%). The performance characteristics of hybrid and conventional evaporators and systems are compared under different conditions. Also, effect of desiccant cycle duration on hybrid system performance is investigated. The obtained results revealed that thin-multilayer alumina bed has substantial effect on hybrid system characteristics. Using the right desiccant layers, hybrid systems achieve better characteristics (smaller evaporator size system and compressor power with higher COP) than conventional system for all the mixing ratios. In the case of pure fresh air, the degree of superheat, pressure ratio and compressor power are lower than those for conventional system by 14.5, 2.0 and 2.7% with higher COP of hybrid system by 12.4%. Short cycle duration has higher sensible heat factor and lower evaporator size while long cycle duration has lower compressor power and higher COP.